Modeling the contribution and benefits of company stakeholders - Irina N. Tkachenko; Irina V. Pervukhina; Aleksandr A. Zlygostev (Управленец, 2020)
The article reviews the theory and methodology and searches for relevant tools for modeling stakeholder contribution and benefits. The methodological framework comprises the stakeholder approach, the concept of sustainable growth and shared values. The study presents two econometric models of stakeholder value contribution and a mathematical model of stakeholder benefits. The models are built on panel data of several Russian banks. The authors look upon banks as constituents of the financial infrastructure essential for the existence of integrated business structures. Our findings show that the most appropriate proxy indicator for modeling monetary stakeholder value is sales revenue. We conclude that, for practical use, it is necessary to explore the relationships between different models and possible ways of their integration and develop a methodology for their evaluation and comparison. Further research should be related to the choice of factors affecting the model, the validity of the choice, the analysis of the regression model in order to infer the stakeholder contribution. To achieve technological breakthroughs, it is important to study value assessment procedures for stakeholders in the conditions of innovative and technological transformation of new forms of business organization, including network-based models, smart industries and ecosystems.